If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 4x + 3y Solving 0 = 4x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 0 + -4x = 4x + -4x + 3y Remove the zero: -4x = 4x + -4x + 3y Combine like terms: 4x + -4x = 0 -4x = 0 + 3y -4x = 3y Divide each side by '-4'. x = -0.75y Simplifying x = -0.75y
| 4x^2-66x+100=0 | | 6x(1+4)=4(4x+1) | | x+70=76 | | 3x+6=4-x | | x-9.34=13.18 | | 364=?-40/100 | | 18=x+14 | | 2x+18=-5x+11 | | cos(65)=1.5 | | 3g-19=4 | | x*(x+1)=2147483647 | | 2a^3+a-2=0 | | x-90+x-22=90 | | (4x-5)/3x | | X+-22=90 | | 5x^2+19x-84=0 | | h=-16t+38t+104 | | X^3-24=75 | | X^2+12x=253 | | 2a^2+5ab-12b^2= | | X^2+12x=p | | 0=.343/tan | | .343/tan | | 15x^2-12x-135=0 | | -5/7-(-1-3) | | -(5/7)-(-1-3) | | 10b^7/2 | | f(x)=10x+lnx | | 21y=(20y+-30) | | 4(a+4)+2a-4= | | 8(x-1)+7=6x+2(-2+x) | | 5(3n+4)=7(7n+1)+7 |